2019
DOI: 10.3390/ma12182965
|View full text |Cite
|
Sign up to set email alerts
|

On the Influence of Capillary-Based Structural Health Monitoring on Fatigue Crack Initiation and Propagation in Straight Lugs

Abstract: This paper addresses the influence on the fatigue life induced by the implementation of a capillary-based structural health monitoring methodology, patented under the name eSHM. It consists in integrating structurally small and pressurized capillaries into the component, so that when a fatigue crack breaches the capillary network, it results in a leak flow to the open atmosphere and loss of pressure in the galleries which is detected by a pressure sensor. The novelty of the proposed system resides in the oppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…A wide range of experimental and numerical studies is reported in the papers in this Special Issue [1][2][3][4][5][6][7][8]. Nazarko and Ziemia ński [1] monitored the axial bolt forces by means of elastic wave propagation signals.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A wide range of experimental and numerical studies is reported in the papers in this Special Issue [1][2][3][4][5][6][7][8]. Nazarko and Ziemia ński [1] monitored the axial bolt forces by means of elastic wave propagation signals.…”
mentioning
confidence: 99%
“…The results showed that the proposed damage detection algorithm is much more efficient than conventional methods [4]. Moonens et al [5] described a promising technology patented under the name effective structural health monitoring (eSHM). In the paper, they addressed the possibility of assessing the fatigue life of a straight lug component by capillary-based structural health monitoring.…”
mentioning
confidence: 99%
See 1 more Smart Citation